INGREDIENTS DEGRADATION IN STEEL FIBER REINFORCED CONCRETE AFTER THERMAL LOADING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The steel fiber reinforced concrete in structures provides good mechanical and physical characteristics and such material applications are increasing. At the same time, if structure is subjected to thermal load it is affecting both properties of reinforcement and matrix as well. The aim of the present research is to investigate the degradation of the characteristics of fibers, randomly distributed in the body of concrete block. A short steel fiber reinforced concrete slabs (400x300x18cm) [1], [2] with homogeneously distributed fibers was undergone to calefaction process from one side. dimension of 16.5x14.5x15 cm) Fiber fracture process was performed based on the single fiber pull-out test by preparing the specimens with fiber from calefacted SFRC block. Experimental curves from each layer were compared with different layer of fibers and investigation had shown that higher load-bearing capacity is there over the thermal loaded fiber. The conclusion were made with the microscopic results and the experimental data.